Islam versus adat in undang-ndang Kedah - Nurul Ain binti Ahmad Sani (Kulliyyah of Islamic Revealed Knowledge ang Human Sciences, International Islamic University Malaysia, 2013)
Kedah is one of the oldest states in Malaysian history. In fact, if we look from the archaeological perspective, some of the earliest sites that are well known in Kedah can be seen through the existence of Lembah Bujang. The ancient state of Kedah has been assumed as one of the significant places in the Malay Annals other than Melaka, and Johor. In other words, the history of Kedah can also be traced if we study deeply the literary sources in order for it to earn the rightful claim to be the most ancient state in the country. Due to the rarity of materials, the early history of Kedah and its relations with its neighbours are vague and incoherent. Perhaps a reliable study of the Kedah state can be looked from the historical perspective with special reference to the Kedah Legal Law. Indeed, the objective of this research is to confirm the aforementioned rightful claim which is outstanding in the Kedah Legal Text by looking at the Islamic and Customary Law.